Ethnobotanical Survey of Medicinal and Aromatic Plants of Bhagalpur Region - Verma, R.K.; Singh, H.N.P.; Thakur, A.K.; Kohli, S.J. (International Journal of Applied Sciences and Biotechnology, 2020)
Medicinal and aromatic plants have been used since the time immortal in different parts on the world including India. Ayurveda provides a detailed insight of different medicinal plants and their use. Different regions of India have a array of different types of medicinal and aromatic herbs. Depending upon climate and soil they may have different degree of pharmacological importance. Lower Gangetic plane present at around eastern part of the Bihar has some sort of Medicinal and Aromatic plants common to Bhagalpur and nearby region. These plants were surveyed on non-agricultural fields of four different localities of Bhagalpur by using quardat method. Abundance, Counts, Cover, Frequency and relative importance were calculated as a whole. About 14 plants were recorded having either well known medicinal or aromatic properties in a total survey area of 1000m2. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 216-222